Pro Sexto Roscio - Cicero, Marcus Tullius; Dyck, Andrew R. (Andrew Roy), 1947- (Cambridge, UK ; New York : Cambridge University Press, 2010)
"Sextus Roscius was murdered in Rome some months after the official end of the Sullan proscriptions on 1 June 81 BC. The case was tried early the following year with a young Cicero acting as defense counsel in his first criminal case for the accused son. Though a novice, Cicero was able to tap into the public anger over the uncontrolled killing and looting of the proscriptions and channel it against the men behind the prosecution, T. Roscius Magnus and T. Roscius Capito. Cicero won a career-making victory, establishing his reputation as a formidable advocate. This, the first new edition of the work in English to be published for almost a century, provides a Latin text and commentary updated to take account of advances in the study of the Latin language as well as Roman institutions, law and society. It is suitable for use with upper-level undergraduates and graduate students"--Provided by publisher.
"When young Cicero rose to plead the case of Sextus Roscius, the prosecutor was visibly relieved that this unknown was his opponent and not one of the established advocates (ʹ60). Once the trial was concluded, there was no case to which he was thought unequal (Brut. 312). This career-making speech contains an almost fully formed approach to juror persuasion and to the psychology of criminality. It is also a risky speech in which the young C. excoriates a favorite of the powerful Sulla besides taking rhetorical risks, especially the purple passage about the parricide's punishment that embarrassed him in later years (Orat.107). If, like Desmoulins' teacher at the Collège Louis-le-Grand, one is put off by the domineering figure of C. the senior statesman,1 this speech shows instead a modest and struggling young orator of great appeal"--Provided by publisher.
Komentar: str. 57-209.
Bibliografija: str. 212-222.
Kazalo
Latin text ; editorial material in English.
Keywords: Ciceron; komentar